O programa Espaço de Brincar do Sesc São Paulo: sua contribuição nas oportunidades de interação entre crianças na primeira infância e seus adultes referência nas vivências - Monteiro, Érica (2023)
The present study is a dissertation that deals with the magnitude of the powers and delicacies of the act of playing, aiming to contribute beyond the conceptions and concepts on the subject, presenting playing as an important element for the global development and learning of all people throughout of life. The research is part of the line of research Early Childhood Education and Play in Educator Training, of the Graduate Program in Education: Curriculum, of the Pontifical Catholic University of São Paulo and is relevant in terms of compiling studies that show the effects of ludic activities in different phases of the development of the human being, in addition to looking for observation reports from educators, about the experiences of mothers who were willing to play with their children, actually getting involved in the playful experiences, reporting the differences observed between before and after playing and what sensations were experienced with the children within an adequate and favorable space for this. Therefore, it is necessary to immerse in the studies of thinkers considered classics in education, and contemporary Brazilian thinkers who discuss education and play, in order to reflect on the place of this phenomenon and the importance of a safe and appropriate space for the ludic experiences can develop. In light of the thoughts of Kishimoto (2007, 2013, 2021), Melis (2011, 2018, 2019), Noffs (2000, 2003, 2016, 2018), Oliveira-Formosinho (2007, 2019), Piaget (2005, 2020, 2021 ), Vygotsky (2008, 2009, 2014), Wallon (2007, 2015) and Winnicott (2021), the research seeks to answer some guiding questions: in which situations can the Espaço de Brincar at Sesc São Paulo contribute to the interaction process between family and child? What are the implications of playing for adults who use the physical space of the Espaço de Brincar Program at Sesc São Paulo? This dissertation has the general objective of defining the Espaço de Brincar at Sesc São Paulo as a space for interaction between adult(s) reference and child - (adult reference is the person - or people - who are taking care of the child at that moment, which may be the mother, father, professional caregivers, teachers), presenting benefits obtained when babies and children in early childhood - up to 6 years old - have the opportunity to play together, with regard to strengthening their affective bond. The specific objectives are to observe the environment as a facilitator of exploration and experiences in playing at all ages; understand what is the attribution of educators in the mediation of playful experiences in the educational environment; to document the existence, importance and power of the Espaço de Brincar Program of Sesc São Paulo as a public leisure facility and non-formal education for early childhood, elucidating its studies on free play, about the use of non-structured material and mainly about the need for the adult reference of the child to be involved in playful activities and in the context of space. The locus of the research is the Espaço de Brincar of Sesc São Paulo - Santo André Unit and the methodology adopted consists of bibliographical and documentary research with a qualitative approach. The data come from consulting reports prepared between 2019, 2021 and 2022, prepared by observing the playful context between families and children, added to dialogic actions carried out with five mothers who frequent the place, whose children are aged between 2 and 5 years. Based on the documents obtained, it can be said that the act of playing influences people's sense of well-being. In the same way, playing with your children provides greater proximity, better quality in the relationship and interaction between them. Therefore, it can be concluded that playing is a fundamental tool for global development throughout life and makes it possible, when in the company of affectionate people, to optimize the quality of interaction between peers, thus contributing to an increase in the bond between they